Preventing XML Problems establishing rules and team policies to prevent poorly written XML. - Kolawa, Dr. Adam (SOA webservices journal.)
Since its inception XML has at times been seen as the cure-all for every problem related to Web applications and integration projects. However, poorly written XML can either slow down an integration project, or worse, cause the integration project to collapse.